Association between six-minute walk distance and prognosis of atherosclerotic coronary heart disease post-cardiac rehabilitation - Ridwan, Muhammad; Sari, Indah P.; Salawati, Liza; Heriansyah, Teuku; Taufiks, Nasyaruddin H.; Putri, Cut JE.; Nurjani, Nurjani (Narra Sains Indonesia, 2023)
Plaque accumulation in the coronary arteries is a major cause of coronary heart disease (CHD), a disease infamously known as a contributor for global death burden. Major adverse cardiac events (MACE) pose significant risks for CHD patients, highlighting the urgency of effective management and cardiac rehabilitation in CHD management. Studies have reported the role of the six-minute walk distance (6MWD) test in predicting outcomes for CHD patients; however, none have performed the investigation in Aceh setting. The aim of this study was to investigate the reliability of 6MWD as a prognostic factor for post-cardiac rehabilitation of patients with atherosclerotic CHD. A cross-sectional study was conducted in Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia. MACE was determined through in-person interviews, and phone calls with 30 atherosclerotic CHD patients who completed cardiac rehabilitation between August 2018 and September 2020. The association between 6MWD and prognosis, assessed by MACE incidence, was calculated. The results revealed that 6MWD was strongly associated with MACE occurrence during post-cardiac rehabilitation (p=0.029; prevalence ratio 4.5). Furthermore, CHD patients achieving 6MWD of more than 300 meters exhibited a lower incidence of MACE (10.5%) than patients with 6MWD of less than 300 meters (45.5%). In conclusion, the present study sheds light on the importance of improving functional capacity in patients with atherosclerotic CHD post-cardiac rehabilitation due to its significant association with the prognosis.